Effect of GDNF on neuroblast proliferation and photoreceptor survival: additive protection with docosahexaenoic acid - Politi, Luis Enrique (2001)
Purpose. In a previous study, it was reported that docosahexaenoic acid (DHA) is essential to postpone apoptosis and to promote differentiation of rat retina photoreceptors in vitro. In the current study, the protective effects of GDNF on photoreceptor cells during development in vitro and its action when combined with DHA were investigated. Methods. Rat retina neuronal cultures were incubated in a chemically defined medium, either without photoreceptor survival factors or supplemented with GDNF, DHA, or GDNF plus DHA. Evolution of survival, apoptosis, opsin expression, mitochondrial functioning, and cell proliferation were investigated at different times of development in vitro. Results. Incubation with GDNF selectively increased the number of surviving photoreceptors, reduced their apoptosis, and augmented opsin expression. Proliferative cell nuclei antigen (PCNA) determination and addition of [3H]-thymidine or bromodeoxyuridine showed that GDNF promoted neuroblast proliferation during the first hours of development in vitro. The combined addition of GDNF and DHA enhanced opsin expression and photoreceptor survival in an additive manner. The advance of photoreceptor apoptosis in cultures without trophic factors correlated with an increased impairment in mitochondrial functionality. Addition of GDNF and DHA significantly diminished the loss of mitochondrial activity. Conclusions. These results show that GDNF stimulated the cell cycle progression, leading to neuroblast proliferation at early stages of development, and delayed the onset of apoptosis later on, improving differentiation and acting as a trophic factor for photoreceptors. The combination of GDNF with DHA had an additive effect both on photoreceptor survival and on opsin expression. Preservation of mitochondrial function may be involved in the antiapoptotic effect of both factors.